We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
686
1
avatar+559 

What is the solution of the equation?

 Mar 1, 2018
 #1
avatar+99702 
+1

 √ [ 2x - 3 ]  + 3  =  x        subtract 3 from both sides

 

 √ [ 2x - 3 ]  =  x - 3        square both sides

 

2x - 3   =  x^2 - 6x + 9       subtract/add   2x, 3  to both sides

 

0  = x^2 - 8x + 12      factor

 

(x - 6) ( x - 2)  = 0

 

Setting each factor to 0  and solving for x  gives x  = 6  and x  =  2

 

Only the first solution solves the original problem

 

 

cool cool cool

 Mar 2, 2018

34 Online Users

avatar
avatar
avatar
avatar